CASH WAQF LINKED SUKUK (CWLS) DALAM PESPEKTIF MASLAHAH MURSALAH (IAIN Tulungagung, 2023)
Cash Waqf Linked Sukuk (CWLS) was born because of the demands of modern times that require everything to be easy, practical and simple. However, behind all the conveniences provided by cash waqf, there is still a fundamental problem, namely the issue of legal legality. The legal status of cash waqf is viewed from the perspective of maslahah mursalah. This research belongs to the category of literature research, while in analyzing the data obtained, the researcher uses a prescriptive analysis approach. The data collection technique used is documentation technique. Cash waqf has been considered valid, because the conditions for maslahah haqiqi (maslahah that are actually realized in real terms in the field), maslahah ammah (maslahah that are general in nature are not only enjoyed by a certain person or group of people), maslahah mulaman bi syar'i (maslahah that is in harmony with and T does not conflict with the Shari'ah) has been fulfilled in cash waqf. So that the legal status of cash waqf is halal. Moreover, the requirements of al habsu ma‟a baqo aynihi (holding goods without losing their essence) also remain in cash waqf.